Find 𝐹(𝑥), if 𝑓(𝑥 − 2) = 𝑥3 + 3𝑥2 − 3𝑥 + 7

1 answer

To find 𝐹(𝑥), we need to substitute (𝑥 + 2) in place of 𝑥 in the equation 𝑓(𝑥 − 2) = 𝑥3 + 3𝑥2 − 3𝑥 + 7:

𝑓(𝑥 − 2) = 𝑥3 + 3𝑥2 − 3𝑥 + 7
𝑓((𝑥 + 2) − 2) = (𝑥 + 2)3 + 3(𝑥 + 2)2 − 3(𝑥 + 2) + 7 (substituting 𝑥 + 2 in place of 𝑥)
𝑓(𝑥) = (𝑥 + 2)3 + 3(𝑥 + 2)2 − 3(𝑥 + 2) + 7

Expanding and simplifying:

𝑓(𝑥) = 𝑥3 + 9𝑥2 + 23𝑥 + 17

Therefore, 𝐹(𝑥) = 𝑥3 + 9𝑥2 + 23𝑥 + 17.
Similar Questions
  1. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 1 answer
  2. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 0 answers
  3. Let equation of an hyperbola be y^2-4x^2+4y+24x-41=0a. Find the standard form b. Find the center c. Find the vertices d. Find
    1. answers icon 0 answers
  4. For the following graph:a. Find the domain of f. b. Find the range of f. c. Find the x-intercepts. d. Find the y-intercept. e.
    1. answers icon 1 answer
more similar questions